2022
DOI: 10.3390/ijms23147921
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Single-Molecule Real-Time Sequencing and Next-Generation Sequencing Eveals Insights into Drought Tolerance Mechanism of Lolium multiflorum

Abstract: Lolium multiflorum is widely planted in temperate and subtropical regions globally, and it has high economic value owing to its use as forage grass for a wide variety of livestock and poultry. However, drought seriously restricts its yield and quality. At present, owing to the lack of available genomic resources, many types of basic research cannot be conducted, which severely limits the in-depth functional analysis of genes in L. multiflorum. Therefore, we used single-molecule real-time (SMRT) and next-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The HOX gene family is involved in several biological processes in plants, such as embryo morphology, meristem development of roots, shoots, and flowers, vascular development, and multiple stress responses, and they are key regulators of plant morphogenesis ( Kikuchi et al, 2015 ). Lui et al performed transcriptome sequencing of L. multiflorum under drought; they found that HOX22 and HOX24 presented high expression levels in leaf samples under drought stress, and they were identified as the enrichment of DEGs in the Intrinsic/Integral component of the Golgi membrane by GO analysis ( Liu Q. et al, 2022 ). These results indicated that IbBBX28 may be involved in drought tolerance by interacting with IbHOX11.…”
Section: Discussionmentioning
confidence: 99%
“…The HOX gene family is involved in several biological processes in plants, such as embryo morphology, meristem development of roots, shoots, and flowers, vascular development, and multiple stress responses, and they are key regulators of plant morphogenesis ( Kikuchi et al, 2015 ). Lui et al performed transcriptome sequencing of L. multiflorum under drought; they found that HOX22 and HOX24 presented high expression levels in leaf samples under drought stress, and they were identified as the enrichment of DEGs in the Intrinsic/Integral component of the Golgi membrane by GO analysis ( Liu Q. et al, 2022 ). These results indicated that IbBBX28 may be involved in drought tolerance by interacting with IbHOX11.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of stress mechanisms in plants, there is also the problem of a lack of high-quality genomes, which prevents in-depth studies. Therefore, researchers have used the combined analysis of triple sequencing and second-generation sequencing data to obtain valuable reference data and the key genes involved in abiotic stress response [ 142 , 143 , 144 ]. In summary, studies of stress often take the form of exploring “differences,” combining transcriptomic techniques to find key nodes or genes for stress resistance at the level of transcriptional regulation and then combining these findings with multi-omics analysis or follow-up studies.…”
Section: Strategies To Improve Plant Growth Under Stressmentioning
confidence: 99%
“…SMRT has been successfully used for high-quality full-length transcript identification and transcriptome analyses in many plant species. It is a high-performance tool used for the elucidation of gene expression dynamics and the molecular mechanisms underlying complex biological processes [ 15 , 16 , 17 ]. To our knowledge, SMRT has not been applied to sudangrass to analyse the mechanisms controlling drought tolerance.…”
Section: Introductionmentioning
confidence: 99%